Financial Strategies and Quality Assurance Implementation in Universities under the COVID-19 Pandemic - Kibalirwandi, Moses Muhindo; Mwesigye, Adrian Rwekaza (Journal of the National Council for Higher Education, 2021)
Introduction/Purpose: Higher education financing strategies for the attraction and retention of students require “collective decision-making” during the COVID-19 pandemic. Quality assurance is a universal reform policy in higher education that encourages participatory leadership. COVID-19 has caused the temporary dismissal of some university staff. Collegiality in some universities is being eroded. The COVID-19 pandemic effects call for re-organisation and strengthening employees to enhance financial strategies as well as platforms to improve collegiality. Desk research utilising a dataset from an ongoing PhD research study on “staff participation in quality assurance implementation in Ugandan universities” has two objectives: 1) to explore causes of Ugandan universities ranking low on the African list of performing universities; and 2) to establish possible financial strategies for attracting and retaining students in Ugandan universities during the COVID-19 pandemic. Methodology: Building on a multi-stakeholder quality assurance theory and adopting a discursive institutional perspective, the study employed a descriptive survey design, using both qualitative and quantitative approaches. University employees, both teaching and non-teaching, participated in the study. Results: Empirical results confirm that causes of ranking low on the African list of performing universities may include, but is not limited to: low funding of research and publication, low morale of employees due to low remuneration or compensation of employees, job insecurity, and promotion in academic ranks being ineffective, and employee mobility. University collegiality is being eroded, and a link between industries and universities is missing. With the outbreak of the COVID-19 pandemic, university employees whose employment contracts were not permanent and pensionable were withdrawn. Parents lost businesses and students’ sponsorship declined. As quality assurance requires normative standards for ensuring the quality of higher education, new strategies and standards need to be established. Generally, the five major criteria (teaching, research, citation, industrial income, and international outlook) of university web ranking have not been given adequate attention before COVID-19. Staff participation and QA policy implementation were positively correlated, where r=0.685; r2 = 0.469, std. error established to be 0.39132, f =123.006, t=5.938, and p=0.000< 0.001. The possible financial strategies were identified as increasing university revenue, considering “revenue side model” rather than “cost side model”. Conclusion: This article contributes to a theoretical debate that employee participation in decision-making towards financial strategies may increase university enrolment and the “throughput” of students. Extending student loan schemes and increasing education-technology enablers with a well-defined “credit policy” and engaging students and staff in productive research may avert the detrimental effects of COVID-19 on higher education institutions. Reform in university education may forcefully be hastened due to the effects and fear of the COVID-19 pandemic. These financial strategies will enable universities to attract and retain students up to completion time.
Keywords: Quality assurance; Students’ loan scheme; Financial autonomy; Effects of COVID-19